Effects of PTEN inhibition on the regulation of Tau phosphorylation in rat cortical neuronal injury after oxygen and glucose deprivation. (28th July 2016) - Zhao, Jing; Chen, Yurong; Xu, Yuxia; Pi, Guanghuan
Abstract: Objective : This report investigated the involvement of the PTEN pathway in the regulation of Tau phosphorylation using an oxygen and glucose deprivation (OGD) model with rat cortical neurons. Methods : Primary cortical neurons were used to establish the oxygen and glucose deprivation (OGD) model in vitro . These were randomly divided into control, OGD, bpV+OGD, As+OGD, Se+OGD and Mock treatment groups. The neuron viability was assessed by MTT, the cell apoptosis was detected using TUNEL staining. The expression of Phospho-PTEN/PTEN, Phospho-Tau/Tau, Phospho-Akt/Akt and Phospho-GSK-3 β /GSK-3 β were detected by Western blotting. Results : OGD induced Tau phosphorylation through PTEN and glycogen synthase kinase-3 β (GSK-3 β ) activation, together with a decrease in AKT activity. Pre-treatment with bpv, a potent PTEN inhibitor, and PTEN antisense nucleotides decreased PTEN and GSK-3 β activity and caused alterations in Tau phosphorylation. Neuronal apoptosis was also reduced. Conclusions : The PTEN/Akt/GSK-3 β /Tau pathway is involved in the regulation of neuronal injury, providing a novel route for protecting neurons following neonatal HI.